2017
DOI: 10.1128/aac.01011-16
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Synergistic Combination Regimens against Carbapenem- and Aminoglycoside-Resistant Clinical Pseudomonas aeruginosa Isolates via Mechanism-Based Pharmacokinetic/Pharmacodynamic Modeling

Abstract: Optimizing antibiotic combinations is promising to combat multidrugresistant Pseudomonas aeruginosa. This study aimed to systematically evaluate synergistic bacterial killing and prevention of resistance by carbapenem and aminoglycoside combinations and to rationally optimize combination dosage regimens via a mechanism-based mathematical model (MBM). We studied monotherapies and combinations of imipenem with tobramycin or amikacin against three difficult-to-treat double-resistant clinical P. aeruginosa isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 67 publications
(101 reference statements)
4
42
0
1
Order By: Relevance
“…These results are matched with previous reports (Yadav et al, 2015;Yadav et al, 2016). The exact mechanism for synergism is not known.…”
Section: Effects Of Aminoglycosides Combinationssupporting
confidence: 92%
“…These results are matched with previous reports (Yadav et al, 2015;Yadav et al, 2016). The exact mechanism for synergism is not known.…”
Section: Effects Of Aminoglycosides Combinationssupporting
confidence: 92%
“…The developed MBM accurately described the antibacterial effects of meropenem and ciprofloxacin in mono-and combination therapies against CW44. The requirement for both subpopulation and mechanistic synergies to describe the antibacterial effects of the combination was similar to that from a previous study with MBM for an aminoglycoside and carbapenem combination (38). Subpopulation synergy, where meropenem killed ciprofloxacin-resistant bacteria and vice versa, was attributable to meropenem and ciprofloxacin having different resistance mechanisms, such as target site mutations (ciprofloxacin), AmpC ␤-lactamase overexpression (meropenem), and an inactivation of outer membrane porin oprD (meropenem) (8).…”
Section: Discussionmentioning
confidence: 56%
“…The life cycle growth model was used to describe the growth and replication of P. aeruginosa (62)(63)(64). We evaluated subpopulation synergy (i.e., meropenem killing the bacteria resistant to ciprofloxacin and vice versa) and mechanistic synergy (i.e., ciprofloxacin enhancing the killing by meropenem against one or multiple bacterial populations) (38,63,65). A diagram of the model structure is shown in Fig.…”
mentioning
confidence: 99%
“…Aminoglycosides in monotherapy have demonstrated substantial bacterial load reduction, but this was followed by rapid and extensive emergence of resistance and ultimately treatment failure (7,8). In the past, in vitro and in vivo studies on carbapenem-aminoglycoside combinations demonstrated synergy (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%